2009
DOI: 10.1016/j.socscimed.2009.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco control policies are egalitarian: A vulnerabilities perspective on clean indoor air laws, cigarette prices, and tobacco use disparities

Abstract: This study models independent associations of state or local strong clean indoor air laws and cigarette prices with current smoker status and consumption in a multilevel framework, including interactions with educational attainment, household income and race/ethnicity and the relationships of these policies to vulnerabilities in smoking behavior. Cross sectional survey data are employed from the February 2002 panel of the Tobacco Use Supplement of the Current Population Survey (54,024 individuals representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 44 publications
(61 reference statements)
4
65
1
Order By: Relevance
“…In Australia, Europe , and the United States, several population-based strategies have been found to be effective in reducing the number of cigarettes smokers consume per day. This includes clean indoor air laws ( Dinno & Glantz, 2009 ;Eriksen & Cerak, 2008 ), media campaigns ( Bala, Strzeszynski, & Cahill, 2008 ;Messer et al, 2007 ;Vallone, Duke, Cullen, McCausland, & Allen, 2011 ), and increased taxation ( Dinno & Glantz, 2009 ). These strategies have also been associated with smokers being categorized in the later stages of the quitting continuum ( DiClemente et al, 1991 ;Dinno & Glantz, 2009 ;Messer, et al, 2007 ;Pierce, Farkas, & Gilpin, 1998 ;Vallone, et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, Europe , and the United States, several population-based strategies have been found to be effective in reducing the number of cigarettes smokers consume per day. This includes clean indoor air laws ( Dinno & Glantz, 2009 ;Eriksen & Cerak, 2008 ), media campaigns ( Bala, Strzeszynski, & Cahill, 2008 ;Messer et al, 2007 ;Vallone, Duke, Cullen, McCausland, & Allen, 2011 ), and increased taxation ( Dinno & Glantz, 2009 ). These strategies have also been associated with smokers being categorized in the later stages of the quitting continuum ( DiClemente et al, 1991 ;Dinno & Glantz, 2009 ;Messer, et al, 2007 ;Pierce, Farkas, & Gilpin, 1998 ;Vallone, et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 900 million smokers (84 percent of all smokers) live in developing and transitional economy countries, while only about 16 per cent live in developed countries, where cigarette consumption decreased significantly in recent decades. Jha and Chaloupka (1999) refer that "in developing countries, smoking increased since 1970, particularly among the poor and less educated".…”
Section: Research Hypothesesmentioning
confidence: 99%
“…However, studies have shown varying responses to price increases among low-income populations. Individuals may compensate for higher prices by relying on low-priced cigarette products (eg, bootlegged or smuggled cigarette products), foregoing other essential goods24–28 or reducing consumption 23 29 30. Critics raise concerns that cigarette taxes are regressive because they disproportionately affect low-income smokers who smoke more and also devote a higher percentage of their income towards purchasing tobacco 31 32.…”
Section: Cigarette Taxesmentioning
confidence: 99%